IMPLEMENTASI PENGATURAN BATAS USIA KAWIN DALAM UNDANG-UNDANG NOMOR 16 TAHUN 2019 TENTANG PERUBAHAN ATAS UNDANG-UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN DI KABUPATEN KARANGASEM - Trinaya Dewi, A.A Mas Adi; Anak Agung Linda Cantika; Dharma Pradana, I Made Dwipayana (Judge : Jurnal Hukum, 2025)
The number of child marriages in Karangasem Regency has increased, reaching 2,000 couples per year. This is despite the fact that Law Number 16 of 2019 concerning Amendments to Law Number 1 of 1974 on Marriage regulates the legal minimum age for marriage in Indonesia. The aim of this study is to examine the implementation of the regulation on the legal minimum age for marriage as stipulated in Law Number 16 of 2019 concerning Amendments to Law Number 1 of 1974 on Marriage in Karangasem Regency, and to identify the obstacles in its implementation. This study employs an empirical legal research method with a descriptive approach. The data used in this research consist of primary and secondary data, collected through observation and interviews. The sampling technique applied is non-probability sampling in the form of purposive sampling. The data are processed using qualitative analysis and presented descriptively. The implementation of the legal minimum age for marriage in Karangasem Regency has not been carried out optimally as mandated by Law Number 16 of 2019 concerning Amendments to the Marriage Law, particularly regarding the minimum legal age for marriage. This shortcoming is due to several contributing factors. The challenges in implementation include factors related to law enforcement, infrastructure/facilities, societal factors, and cultural or legal culture factors. There is a need for synergy between the local government and the community to conduct outreach and prioritize the equitable implementation of the legal minimum age for marriage in Karangasem Regency.